Assessing chronic musculoskeletal pain in horses and the effectiveness of the administration of paracetamol in addition to non-steroidal anti-inflammatories for chronic pain - Pratt, Stefanie (2025)
Equine lameness is a common problem which affects both equine athletes and geriatric horses, with geriatric horses being at increased risk of lameness (BlueCross, 2018, Ireland et al., 2011). Lameness leads to a shortened working career, increased financial losses and reduction in welfare (Ireland et al., 2012, Marshall et al., 2012). Lameness is also very important to owners, however there is significant under recognition of lameness by owners (Dyson et al., 2017, McGowan et al., 2010). As lameness is a manifestation of pain due to a musculoskeletal injury, when lameness is not recognised horses can continue to be worked leading to compromised welfare (Vinuela-Fernandez et al., 2011). Recognition of musculoskeletal pain relies on assessments including pain scales, subjective lameness grading scales and objective technologies including forceplates, kinematic technology and inertial measurement units. Subjective lameness grading scales have been shown to have marginal agreement between observers especially when considering mild or hindlimb lameness (Dyson, 2011, Hammarberg et al., 2016, Keegan et al., 2010). Objective gait analysis systems may be more reliable especially when considering mild lameness. A narrative review briefly compared both objective and subjective gait analysis systems (Crecan and Peștean, 2023), however there are currently no published systematic reviews which compare the effectiveness of subjective and objective gait analysis.